The effect of nonylphenolethoxylate on lightweight concrete / Ahmad Khairil Shahibi - Shahibi, Ahmad Khairil (1997)
Lightweight concrete is a concrete lighter than the conventional concrete made from lightweight aggregate or in the form of aerated concrete. This project analyzed the effect of NONYLPHENOLETHOXYLATE as an air-entraining agent to lightweight concrete. The experimental program comprised of design mix cement: sand ratio namely 1:3 and Nonylphenolethoxylate dosages of 50 ml, 75 ml, 100 ml, 300 ml, and 500 ml per 100 kg of cement. The strength development test carried out on 150 mm cube are at 3, 7, and 28 days curing. The Figg-air method for determining the air permeability by using a pressure difference of one atmosphere is carried out on 150 mm cube at 28 days curing. It is known that density and strength of lightweight concrete is lower than normal concrete. It can be produced with a density range of approximately 300 to 2000 kg/m3 and cube strengths of approximately between 1 and 60 N/mm2. These values can be compared to those for normal density concrete of approximately between 2100 and 2500 kg /m3, and cube strengths of between 15 and 100N/mm2.